Interaction between Levodopa and Methyldopa. Issue 5858 (14th April 1973) - Gibberd, F. B.; Small, Elizabeth
Abstract : The interaction between methyldopa and levodopa was studied in 18 patients with Parkinsonism. Together they produced a fall in blood pressure in doses which when given alone had no effect or only a slight hypotensive effect. Severe hypotension never occurred. It is reasonable to give methyldopa to hypertensive patients on levodopa but the regimen should be initiated in hospital.